Teacher Empowerment Through The Toping Method in Visiting Teacher Activities to Improve Pedagogic Competence - Rabya Mulyawati Ahmad; Ramadan Mulyawan Ahmad; Syaban Setyawan Ahmad; Asliat Hinggi Guhir (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
The quality of education in border areas, such as the Timor Tengah Utara (TTU) Regency, often faces challenges in improving teacher competencies. This community service program aims to empower teachers through the Gasing method (Easy, Fun, and Enjoyable) as part of the Visiting Teacher program. This method was chosen because it is effective in helping teachers improve their pedagogical competence. The program involved teacher working groups (KKG) and subject teacher working groups (MGMP) in TTU over three days, from September 26 to 28, 2024. Training and hands-on practice sessions were conducted to equip teachers with the skills to apply the Gasing method in their teaching. The analysis results showed a significant improvement in the teachers' average understanding, rising from 55.8 before the training to 87.07 afterward. Additionally, observations recorded high levels of participant engagement. Question-asking activities reached 88%, the ability to answer facilitators' questions was 92%, group discussions demonstrated 84% engagement, and the active application of new Gasing techniques reached 96%. Overall, 90% of the teachers displayed excellent engagement across various aspects, reflecting the program's effectiveness. This initiative not only improved teachers' understanding but also fostered a more enjoyable and effective learning environment. The implementation of the Gasing method holds significant potential to enhance teaching quality, not only in TTU but also in other regions with similar characteristics, contributing to the advancement of education